Pedagogical possibilities for unruly bodies. Issue 5 (4th July 2018) - Rice, Carla; Chandler, Eliza; Liddiard, Kirsty; Rinaldi, Jen; Harrison, Elisabeth
ABSTRACT: Project ReVision uses disability arts to disrupt stereotypical understandings of disability and difference that create barriers to healthcare. In this paper, we examine how digital stories produced through ReVision disrupt biopedagogies by working as body-becoming pedagogies to create non-didactic possibilities for living in/with difference. We engage in meaning making about eight stories made by women and trans people living with disabilities and differences, with our interpretations guided by the following considerations: what these stories 'teach' about new ways of living with disability; how these stories resist neoliberalism through their production of new possibilities for living; how digital stories wrestle with representing disability in a culture in which disabled bodies are on display or hidden away; how vulnerability and receptivity become 'conditions of possibility' for the embodiments represented in digital stories; and how curatorial practice allows disability-identified artists to explore possibilities of 'looking back' at ableist gazes.